2021
DOI: 10.1097/pr9.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective chart review of perioperative pain management of patients having surgery for closed ankle fractures using peripheral nerve blocks at a level one trauma center

Abstract: Introduction: Chronic opioid use is unfortunately perceived among these postoperative patients, specifically within orthopedic surgery. Patients having orthopedic surgeries are at risk for becoming addicted to opioids, and one benefit of peripheral nerves blocks could be to provide an alternative mode of pain control. This study takes a retrospective look at the use of peripheral nerve blocks for pain control following surgery for isolated traumatic ankle injuries. We hypothesize that when peripheral nerve blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…5 Several studies have shown that the use of a peripheral nerve block significantly decreases opioid use in the first 24-72 hours post-op. [15][16][17][18][19][20][21][22] While the studies that have looked into the effectiveness of peripheral nerve blocks for postoperative pain management lack consistency in outcome variables, nearly all collected data on postoperative inpatient opioid dosing. Despite variation in included outcomes, every study reviewed in this article showed a significant reduction in postoperative inpatient opioid dosing.…”
Section: Postoperative Inpatient Opioid Usementioning
confidence: 99%
“…5 Several studies have shown that the use of a peripheral nerve block significantly decreases opioid use in the first 24-72 hours post-op. [15][16][17][18][19][20][21][22] While the studies that have looked into the effectiveness of peripheral nerve blocks for postoperative pain management lack consistency in outcome variables, nearly all collected data on postoperative inpatient opioid dosing. Despite variation in included outcomes, every study reviewed in this article showed a significant reduction in postoperative inpatient opioid dosing.…”
Section: Postoperative Inpatient Opioid Usementioning
confidence: 99%